Inhalation therapy for repairing damaged elastin fibers and decelerating elastinolysis in chronic obstructive pulmonary disease. (4th May 2018) - Janssen, Rob; Piscaer, Ianthe; Wouters, Emiel FM.
ABSTRACT: Introduction : Current pharmacologic therapy of chronic obstructive pulmonary disease (COPD) can reduce respiratory symptoms and exacerbation frequency. However, no single COPD intervention except for lung transplantation has proven effective in recovering lung function. Lung elasticity is reduced in COPD lungs, which is for a large part due to chronically enhanced elastin degradation. Elastin calcification and formation of advanced glycation end products (AGEs) may also contribute to this. Areas covered : We propose inhalation therapy to induce repair of damaged pulmonary elastin fibers by stimulating tropoelastin synthesis, assembly and crosslinking in order to improve lung function in patients with COPD. Decelerating elastinolysis is another treatment objective, as well as decalcification and deglycation of the extracellular matrix. Expert commentary : Studies should be conducted to test whether it is feasible to restore pulmonary elastin fibers with inhalation therapy. We expect that the optimal formulation will turn out to be a combination of copper, epigallocatechin-(3-)gallate or pentagalloyl glucose, vitamin A/D/K, magnesium, heparin or heparan sulfate, minoxidil and one or more AGEs inhibitors. Establishing a treatment that has the proven ability to facilitate regain of lost lung function in COPD patients would cause a major paradigm shift in this debilitating disease.